Method for Screening of Malaysian Biomass Based on Aggregated Matrix for Hydrogen Production through Gasification - Abdullah, SS (Asian Network for Scientific Information, 2010)
Screening and evaluating various biomass for their potential as gasifier feedstocks can be a very complex and time consuming works. To optimize time of screening and selecting a promising fuel for gasifier, a novel method for screening of biomass using an aggregated matrix is introduced. Eleven Malaysian biomass from various resources are characterized and subsequently screened using this method based on their calorific value, O:C and H:C ratios, moisture, ash, volatiles and fixed carbon content. From the results obtained, palm kernel shell, sawdust and coconut shell are the most preferred biomass for gasification as each of these samples obtained 12 points from the aggregated matrix. The least preferred is empty fruit bunch, with only 8 points. Rubber seed kernel and coconut fiber scored 10 points while the other biomass scored 9 points. Through this novel and flexible method, users such as researchers or industrial practitioner who have limitations such as time and equipment availability are able to do an efficient screening of multiple feedstocks for their systems